Specific Repression of Phosphoribosylpyrophosphate Synthetase by Uridine Compounds in Salmonella typhimurium - Olszowy, Joyce (1972)
Mutants of Salmonella typhimurium with specific pyrimidine requirements were used to demonstrate that only uridine compounds exert repressive control over synthesis of phosphoribosylpyrophosphate synthetase.